KONFLIK KELUARGA LUAS DALAM PENGELOLAAN TAMBANG EMAS DI NAGARI KOTO BARU KECAMATAN IV NAGARI KABUPATEN SIJUNJUNG - Suriya, Sri - (Pendidikan Sosiologi, 2014)
This thesis describes about extended family conflict in managing gold mining Nagari Koto Baru Kecamatan IV Nagari Kabupaten Sijunjung, where this conflict was become by struggle the land or location that will be mined. Related the problem, the question of this research is who and how the extended family conflict in managing gold mining. The purpose of this research is to describe the form of extended family conflict conflict in managing gold mining.On this research, the writer uses Lewis Coser theory, it is because of according to Coser to avoid the conflict to more sharply required valve rescuers. The Approach used on this research is qualitative research method with descriptive types for giving the details overview from the reality researched. Collecting the data is done by non participant observation and deep interview. Research informant by purposive sampling (interview is done based on the certain criteria). Unit data analysis is family and data analysis that be used by step data collection, data reduction, data presentation and conclusion.Based on the final result of the research that have been done, extended family conflict have become between uncle and nephew, also it is become among sibling relationship who have tied the maternal lineage on the same tribes. These conflicts occur because of the presence of each other for the right on land ownership on mines. Whereas, the form of extended family conflict is dispute, so that war arguments, shouting hardly, and also there are threat that is done to the people who mine the gold. In solving the extended family conflicts at Nagari Koto Baru is done by discussion and conference among two sides. The conflict that could not be solved by formal institution,like Niniak Mamak will be solved by police institution. This extended family conflict will be solved by Niniak Mamak by meeting two sides for getting the decission. The final decission is to devide the mining to be two parts, likewise the conflict that happened between uncle and nephew as well as conflict that happened on the sibling relationship.